An urban–rural spotlight: evolution at small spatial scales among urban and rural populations of common ragweed. Issue 1 (24th February 2021) - Kostanecki, Adam; Gorton, Amanda J; Moeller, David A
Abstract: Urbanization produces similar environmental changes across cities relative to their neighboring rural environments. However, there may be high environmental heterogeneity across an urban–rural gradient. Previous research in Minneapolis, MN, USA, found mixed evidence that urban and rural plant populations of common ragweed have locally adapted and that urban populations exhibit greater among-population divergence in ecologically-important traits. To investigate whether there are parallel patterns of urban–rural trait divergence across different urban areas, we examined trait variation across an urban–rural gradient in a second city, St. Louis, MO, USA. We used growth chamber and greenhouse common environments to investigate variation in six traits within and among 16 populations of common ragweed (eight from each urban and rural area). Urban and rural plants diverged significantly in three of five traits, with rural plants having lower percent germination, greater height and lower leaf dissection index. We also found greater variance in plant height among urban compared to rural populations, potentially driven by heterogeneity in human management practices on urban populations. Patterns of urban-rural trait divergence (e.g. in flowering time) differ substantially from those found previously in the reciprocal transplant experiment in Minneapolis, contradicting the hypothesis of parallel evolution across different metropolitan areas. The results of this study suggest that there is considerable population variation in ecologically-important traits, but that urban populations do not consistently differ from neighboring rural populations.